Industry growth health impact on a mining Peruvian mountain city inhabitants - RAMÍREZ, AUGUSTO (2004)
Objective: To determine incipient industrialisation health impact on the population of a mining Peruvian mountain city. Material and Methods: Retrospective descriptive study that reviewed Regional City Medical Hospital patient’s records seen from 1996 through 2001, searching for environmental related illnesses. We used growth indexes and compared them statistically with environmental indexes by logistic regression using the SPSS/6,1. Results: We found significant correlation (95% confidence index) between industrial growth indexes and health status, such as increase of the number of vehicles and respiratory illnesses (p=0,0001), number of vehicles and dermatological illnesses (p=0,0003), number of vehicles and conjunctivitis (p=0,0001). Significance was less when comparing gold/silver production (p=0,01, 0,003 and 0,0045, respectively) with lead mining production (p=0.03, 0,001, and 0,39, respectively). There was no significance when comparing industrial development with dairy production and population increase (p=0,019, 0,04). Conclusions: Increase in industrial activity correlates with environmental illnesses. We recommend performing further scientific studies to assess environmental pollution index to allow the city to properly manage environmental pollution.